(3GdJMOjGJ GdeSJbHdjI ddJcJd GdEbJUGOj GdYQHj (B:s (3GdYhdeI hGdJcdGJ GdEbdjejI (B/s - (3YHO GdQMje, EcQGes ((3GdEScfOQjI(B: s (3ecJHI eOHhdj(B, s, 2002)
(3GdeJZjQGJ GdOhdjI hGdEbdjejI(B- (3GdJcJd GdEbJUGOj GdEbdjej eagheg hCgejJg hCTcGdg(B- (3JcJdGJ GdEbJUGOj GdYQHj hJMOjGJ GdYhdeI GdEbJUGOjI(B- (3JcJdGJ GdEbJUGO GdYQHj hJMOjGJ GdeTQhYGJ GdEbdjejI GdHOjdIs
Keywords: (3GdEbJUGOs; (3GdJcJdGJ GdEbJUGOjI (B- (3GdOhdjIs; (3GdYhdeIs